Pain and Death in O Monstro by Humberto De Campos (Global Journal of Human-Social Science, 2023)
This article aims to investigate the construction of Pain and Death in O Monstro by Humberto de Campos In the narrative there are three dominant characters Pain Death and Man Death is present in literature since ancient civilization as can be seen in Gilgamesh written in Mesopotamia probably around the years 2150 - 1400 BCE to the present days as a driving force of narratives Therefore we will look for authors who dealt with the relationship between death pain and man in the literary universe As a theoretical support we will build on the literary scholarship of Edgar Morin 1997 and Philippe Ari s 2012 Hoggard 2022 and Sonja Loidl 2010
Keywords: death; pain; humberto de campos; the monster